Pengaruh Jenis Foundation Terhadap Hasil Rias Wajah Pesta - Naseha Sainah, Desi Putri Ramadona; Naseha Sakinah; Siska Miga Dewi (Universitas Negeri Jakarta, 2023)
The results of applying party makeup foundation using foundation cake, based on observation assessment and statistical calculations, showed that the highest value was in the smoothness aspect of 3.40, with very smooth criteria; the observer's success rate had an average value of 3.40 with very successful criteria, and the durability level had an average value of 3.30 with very resistant criteria. The results of applying party makeup foundation using foundation cream, based on observation assessment and statistical calculations, showed that the highest value was in the observer's success rate aspect of 3.30, with very successful criteria; the smoothness level had an average value of 3.20 with very successful criteria, and the durability level had an average value of 2.90 with very resistant criteria. Foundation is a cosmetic that serves as the basis of makeup, offering many functions and correcting the face. It comes in various forms and colors. By using foundation, the texture of the face will look smoother and even. The foundation consists of several types, namely liquid foundation, compact foundation, cream foundation, and stick foundation.